Fārsī adab bah ʻahd-i Bahādur Shāh Ẓafar - Ak̲h̲tar, Abūlḥasan (Ghausī : Taqsīmkār, Aʻẓamī Buk Ḍipo, 1998)
Evolution of Persian literature in India during 19th century.
Includes bibliographical references (p. 387-396).
Mode of access: Internet.
In Urdu.
Keywords: Persian literature -- 19th century -- History and criticism; Persian literature -- India -- History and criticism